Self-Supporting Arch Halls – Design Methods - Walentyński, Ryszard; Cybulski, Robert; Myrcik, Henryk (Engineering Transactions, 2026)
Self-supporting arch halls are increasingly used for the construction of buildings with a significant impact on public safety. Unfortunately, no specific design methodology has been established yet. Even more concerning is the growing emergence of new design challenges, including local structural modifications and unconventional loading conditions. This study reviews methods applied in engineering practice as well as those proposed in research studies. A comparative analysis of the results obtained using various methods is presented for selected structures subjected to loads according to applicable standards.